Novel Lung Growth Strategy with Biological Therapy Targeting Airway Remodeling in Childhood Bronchial Asthma - Mitsuru Tsuge; Masanori Ikeda; Hirokazu Tsukahara (MDPI AG, 2022)
Anti-inflammatory therapy, centered on inhaled steroids, suppresses airway inflammation in asthma, reduces asthma mortality and hospitalization rates, and achieves clinical remission in many pediatric patients. However, the spontaneous remission rate of childhood asthma in adulthood is not high, and airway inflammation and airway remodeling persist after remission of asthma symptoms. Childhood asthma impairs normal lung maturation, interferes with peak lung function in adolescence, reduces lung function in adulthood, and increases the risk of developing chronic obstructive pulmonary disease (COPD). Early suppression of airway inflammation in childhood and prevention of asthma exacerbations may improve lung maturation, leading to good lung function and prevention of adult COPD. Biological drugs that target T-helper 2 (Th2) cytokines are used in patients with severe pediatric asthma to reduce exacerbations and airway inflammation and improve respiratory function. They may also suppress airway remodeling in childhood and prevent respiratory deterioration in adulthood, reducing the risk of COPD and improving long-term prognosis. No studies have demonstrated a suppressive effect on airway remodeling in childhood severe asthma, and further clinical trials using airway imaging analysis are needed to ascertain the inhibitory effect of biological drugs on airway remodeling in severe childhood asthma. In this review, we describe the natural prognosis of lung function in childhood asthma and the risk of developing adult COPD, the pathophysiology of allergic airway inflammation and airway remodeling via Th2 cytokines, and the inhibitory effect of biological drugs on airway remodeling in childhood asthma.